Peripheral neuropathy and its clinical correlates in Type 2 diabetic subjects without neuropathic symptoms in Nnewi, South-Eastern Nigeria - Ogonna Celestine Oguejiofor; Chikezie Hart Onwukwe; Chidiebele Malachy Ezeude; Ejike Kenneth Okonkwo; Justin Chibueze Nwalozie; Charles Uzoma Odenigbo; Charlotte Blanch Oguejiofor (Journal of Diabetology, 2019)
Background: Peripheral neuropathy (PN) is a risk factor for foot disease in type 2 diabetes mellitus (T2DM). There are scanty data on prevalence of PN and its clinical correlates in Nigerian T2DM subjects without neuropathic symptoms. Objectives: To evaluate the prevalence and clinical correlates of PN diagnosed using objective methods in T2DM subjects without symptoms of PN. Materials and Methods: This is a cross-sectional study involving T2DM subjects at the Diabetes Clinic of Nnamdi Azikiwe University Teaching Hospital (NAUTH), Nnewi, Nigeria. History was obtained and physical examination done on subjects. Fasting plasma glucose (FPG) done on the day of assessment and values of glycated haemoglobin (HbA1c), and fasting lipid profile done within the preceding three months- were obtained from subjects' clinic folders. Diabetic Neuropathy Symptom Score (DNSS) was used to identify subjects without neuropathic symptoms. PN was diagnosed using tuning fork, and two biothesiometers. Data collection was done using researcher-administered study proforma. Data were analyzed using SPSS version 20. Results: 524 subjects [244 (46.6%) males and 280 (53.4%) females] were recruited for the study. 223 (42.6%) of these subjects did not have neuropathic symptoms and PN tested further with 3 objective methods. PN prevalence with tuning fork, analog and digital biothesiometers were 71.5%, 14.8% and 14.8% respectively. All clinical variables evaluated were poor predictors of PN (P > 0.05). Conclusion: PN diagnosed by objective methods is present in South-Eastern Nigerian T2DM subjects who do not have symptoms of PN. Tuning fork diagnosed PN much more than the other methods reflecting its subjectivity.